An Insightful Exploration: Business Analytics Internship at Talent Corner - Kamble, Rutuja (ATLAS SkillTech University, 2025)
This report presents a detailed account of the internship I did at Talent Corner, which is an Indian independent HR management company set up in 2002. Over the years, Talent Corner has grown tremendously, and today it works with more than 200 team members across 15 locations, servicing above 900 clients across most diverse industries. The major tasks performed by me during the internship period included: getting an understanding of different departments in the company and their functions; conducting extensive data analysis across various sectors; rendering assistance in different administrative tasks, such as the maintenance of the office website and franchise accounts; and analysing the historical company data to provide strategic recommendations for the enhancement of revenue. This was an intensive experience in terms of insight into the global human resources service industry and the business analytics segment with a view to optimize recruitment processes. During this internship, I gained more than just an insight into human resources and business analytics; it contributed much towards my professional growth, equipping me with practical skills and knowledge that shall be invaluable in my future career.
Project Report on An Insightful Exploration: Business Analytics Internship at Talent Corner (2023-2025) Under the Guidance of Prof. Shashikant Patil
Keywords: human resources; business analytics; professional growth